The impact of fasting toward oxidative stress marker in the liver and plasma of new zealand white rabbit - Novi Silvia Hardiany; Stephanie Gosal; Damayanti Angelina; Engelbert Julyan Gravianto; Radiana Dhewayani Antarianto (Indonesian Society for Biochemistry and Molecular Biology, 2022)
Background: Fasting may increase the activity of endogenous antioxidants and protect against oxidative stress. However, the effects of different fasting durations on the liver have not been reported. Objective: The purpose of this study is to determine the effect of intermittent and prolonged fasting on oxidative stress markers in the liver tissue and plasma of New Zealand White rabbits. Methods: New Zealand White rabbits were divided into three groups: control, intermittent fasting (IF), and prolonged fasting (PF), with each group consisting of five rabbits. The control group was provided with food ad libitum; the IF group fasted for 16 hours, while the PF group fasted for 40 hours, followed by an eight-hour non-fasting period for six days. In liver tissue and plasma, oxidative stress indicators (catalase, carbonyl, GSH) were evaluated. Results: In the IF group, liver GSH was significantly higher than in the control group. However, neither liver carbonyl nor catalase levels changed significantly in the IF group. In the IF group, plasma carbonyl was significantly lower than in the PF group. In addition, there was no significant differences between groups in plasma catalase and GSH levels. Conclusion: Intermittent fasting and prolonged fasting could significantly increase liver GSH levels of New Zealand White rabbits. In addition, intermittent fasting is more effective than prolonged fasting at preventing oxidative stress.